2010
DOI: 10.1203/pdr.0b013e3181c34609
|View full text |Cite
|
Sign up to set email alerts
|

Majority of Dietary Glutamine Is Utilized in First Pass in Preterm Infants

Abstract: Glutamine is a conditionally essential amino acid for very low-birth weight infants by virtue of its ability to play an important role in several key metabolic processes of immune cells and enterocytes. Although glutamine is known to be used to a great extend, the exact splanchnic metabolism in enterally fed preterm infants is unknown. We hypothesized that preterm infants show a high splanchnic first-pass glutamine metabolism and the primary metabolic fate of glutamine is oxidation. Five preterm infants (mean … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
15
0

Year Published

2011
2011
2017
2017

Publication Types

Select...
5
2
1

Relationship

1
7

Authors

Journals

citations
Cited by 25 publications
(17 citation statements)
references
References 37 publications
2
15
0
Order By: Relevance
“…Several factors, such as variability in protein and energy content of human milk, insufficient enteral macronutrient absorption [33] in the early postnatal period, earlier reduction and cessation of PN, and first-pass utilization of proteins by the intestine [34], might contribute to this finding and may also explain the poorer gain in head circumference in 2010.…”
Section: Discussionmentioning
confidence: 99%
“…Several factors, such as variability in protein and energy content of human milk, insufficient enteral macronutrient absorption [33] in the early postnatal period, earlier reduction and cessation of PN, and first-pass utilization of proteins by the intestine [34], might contribute to this finding and may also explain the poorer gain in head circumference in 2010.…”
Section: Discussionmentioning
confidence: 99%
“…Comparable values have been described in healthy adults after a meal21 and in enterally fed piglets 37. There is discussion about correcting protein intake for SPE in calculations of WbPBal, since these retained amino acids are used for constitutive or secreted (glyco-)proteins in the gut,38 39 which is then considered part of WbPS. We have therefore also calculated the data without correction for SPE (not shown) and found that protein breakdown was 15–19% lower and protein balance 2.7–3.9 times higher.…”
Section: Discussionmentioning
confidence: 99%
“…Furthermore, high protein utilisation by the rapidly growing intestine may further decrease systemic protein availability when administered enterally 38. Therefore, macronutrient calculation should take into account that absorption and bioavailability of enterally administered nutrients will be incomplete early on.…”
Section: Enteral Nutritionmentioning
confidence: 99%